Routine use of gene panel testing in hereditary breast cancer should be performed with caution. (December 2016) - van Marcke, Cedric; De Leener, Anne; Berlière, Martine; Vikkula, Miikka; Duhoux, Francois P.
Highlights: Gene panel testing for hereditary breast cancer is not ready for daily practice in offices of non-genetic specialties. It generates more variants of unknown significance than clinically useful variants. Only a minority of the included genes are clinically useful. Large public databases should gather all the results for continuous research. Only pathogenic variants in rigorously validated genes should lead to specific management. Abstract: Breast cancer is the most frequent cancer occurring in women. Ten percent of these cancers are considered hereditary. Among them, 30% are attributed to germline mutations in the tumor suppressor genes BRCA1 and BRCA2 . Other genes of lower penetrance are also known, explaining together up to 40% of the hereditary risk of breast cancer. New techniques, such as next-generation sequencing, allow the simultaneous analysis of multiple genes in a cost-effective way. As a logical consequence, gene panel testing is entering clinical practice with the promise of personalized care. We however advocate that gene panel testing is not ready for non-specialist clinical use, as it generates many variants of unknown significance and includes more genes than are presently considered clinically useful. We hereby review the data for each gene that can change the risk management of patients carrying a pathogenic variant.